Budget cap and pay-back model to control spending on medicines: A case study of Bulgaria - Mitkova, Zornitsa; Dimitrova, Maria; Doneva, Miglena; Tachkov, Konstantin; Kamusheva, Maria; Marinov, Lyubomir; Gerasimov, Nikolay; Tcharaktchiev, Dimitar; Petrova, Guenka (Frontiers in Public Health, 2022)
Central and Eastern European countries (CEEC) have among the highest rates of increase in healthcare expenditure. External reference pricing, generics and biologics price capping, regressive scale for price setting, health technology assessment (HTA), and positive drug lists for reimbursed medicines are among the variety of implemented cost-containment measures aimed at reducing and controlling the rising cost for pharmaceuticals. The aim of our study was to analyze the influence of a recently introduced measure in Bulgaria—budget capping in terms of overall budget expenditure. A secondary goal was to analyze current and extrapolate future trends in the healthcare and pharmaceutical budget based on data from 2016 to 2021. The study is a retrospective, observational and prognostic, macroeconomic analysis of the National Health Insurance Fund's (NHIF) budget before (2016–2018) and after (2019–2021) the introduction of the new budget cap model. Subgroups analysis for each of the three new budget groups of medicines (group A: medicines for outpatient treatment, prescribed after approval by a committee of 3 specialists; group B: all other medicines out of group A; and group C: oncology and life-saving medicines out of group A) was also performed, and the data were extrapolated for the next 3 years. The Kruskal–Wallis test was applied to establish statistically significant differences between the groups. During 2016–2021, healthcare services and pharmaceutical spending increased permanently, observing a growth of 82 and 80%, respectively. The overall healthcare budget increased from European €1.8 billion to 3.3 billion. The subgroup analysis showed a similar trend for all three groups, with similar growth between them. The highest spending was observed in group C, which outpaced the others mainly due to the particular antineoplastic (chemotherapy) medicines included in it. The rising overall healthcare cost in Bulgaria (from European €1.8 billion to 3.3 billion) reveals that implementation of a mechanism for budget predictability and sustainability is needed. The introduced budget cap is a relatively effective measure, but the high level of overspending and pay-back amount (from European €34 billion to 59 billion during 2019–2021) reveals that the market environmental risk factors are not well foreseen and practically implemented.